The clinical atlas of Parkinson's disease - Nicholl, D. J.; Williams, A. (Oxford : Blackwell, 2003)
Contains over 80 video clips covering the differential diagnosis and management of Parkinson's disease; some 400Mb in total
System requirements: Windows 95/98/NT/2000/XP, Pentium Processor, 64 MB of RAM (or greater), 8 x CD-ROM (or greater), 800 x 600 screen resolution (or greater), QuickTime
System requirements : Macintosh; OS 9.2 (or greater), G4 processor, 64 MB of RAM (or greater), 8 x CD-ROM (or greater), 800 x 600 screen resolution (or greater), QuickTime
Keywords: Parkinson Disease -- diagnosis; Parkinson Disease -- atlases; Parkinson Disease -- CD-ROM